Global and local strain rate sensitivity of bimodal Al-laminates produced by accumulative roll bonding. (15th January 2016) - Ruppert, Mathis; Schunk, Christopher; Hausmann, Daniel; Höppel, Heinz Werner; Göken, Mathias
Abstract: Laminated metallic composites of 5 mm thickness, with a bimodal grain size distribution and alternating layers of commercial purity aluminum (Al99.5) and high purity aluminum (Al99.999) were successfully processed by accumulative roll bonding at room temperature up to 8 cycles. With increasing number of ARB cycles the layers of commercial purity aluminum become ultrafine-grained, whereas the grain size in the high purity aluminum remains clearly above 1 μm. The mechanical properties of the laminates were investigated by compression testing with strain rate jumps and by nanoindentation using continuous stiffness method and nanoindentation strain rate jump tests. Thereby the strain rate sensitivity was determined both globally, proving the bulk laminate material, and locally, proving the single layers of the laminate. It was found that the local strain rate sensitivity of the ultrafine-grained Al99.5-layers is increasing up to 4 ARB cycles, while the local strain rate sensitivity of the coarse grained Al99.999-layers remains rather constant independently of the number of cycles. In contrast to that, the global strain rate sensitivity of the bulk laminate increases up to 8 cycles without saturation. Thermally activated annihilation of dislocations at the grain boundaries and interfaces between the coarse grained and ultrafine-grained layers is proposed in order to interpret the findings. Graphical abstract: